SUDUT PANDANG HUMAN RIGHTS WATCH MENGENAI ISU KEJAHATAN KEMANUSIAAN DAN KEKERASAN SEKSUAL DI SUDAN SELATAN - Wihelmina Melissa; Camila Tatya Nadida; Riany Linggar Sari; Ida Kurnia (PROSIDING SERINA, 2021)
“ Human Rights Watch's Perspective on the Issue of Crimes Against Humanity and Sexual Violence in South Sudan “ Research is based on crimes against humanity and sexual violence in South Sudan, East Africa. This case starts from a civil war and it started became a serious violence like crimes against humanity on international levels, sexual violence, food crisis, torture, slaughter and even murder is something that South Sudanese people often face regardless of age. There are so many minors and innocent woman become victims of torture. Even civilians are limited in voicing their aspirations and expression. There are so many bad things that happened to the South Sudanese people. In this case, we the writers discuss this issue from the perspective of Human Rights Watch. Human Rights Watch is an international organization who act as part of the great spirit movement of the victims to keep fighting to protect dignity and promote human rights. The purpose of this research is explain aspects of Human Rights Watch's response to the issues of crimes against humanity and sexual violence in South Sudan. We use the secondary data and qualitative data for the descriptive method of writing in this journal which explains the subject matter of the existing secondary data. Therefore, Human Rights Watch can provide patronage to the Sudanese people in South Sudan.